MINI REVIEW: PEMBUATAN DYE SENSITIZED SOLAR CELL (DSSC) MENGGUNAKAN SEMIKONDUKTOR TIO2 DENGAN ZAT WARNA ANTOSIANIN - Ziyyanatul Luthfiyyah; Noor Hindryawati; Irfan Ashari Hiyahara (PROSIDING SEMINAR KIMIA, 2022)
Dye Sensitized Solar Cell (DSSC) is a tool or device that can convert light energy into electrical energy. Dye Sensitized Solar Cell (DSSC) is a solar cell consisting of a pair of glass electrodes, namely the working electrode and the counter electrode flanking the electrolyte. The working electrode is composed of TCO (Transparent Conducting Oxide) glass which is then coated with TiO2 and a dye containing anthocyanins as a charge carrier photosensitizer. The counter electrode is composed of TCO glass coated with carbon which is used as a catalyst to accelerate the redox reaction with the electrolyte. Anthocyanins can absorb photon energy at a distance of about 520-550 nm. Dye will excitate due to absorption of photon energy. The more dye attached, it will produce more photoelectrons where the size of the TiO2 semiconductor affects the dye attached or attached during the coloring process. Natural anthocyanins can be obtained from plant materials such as the crown of the gods, dragon fruit, red cabbage, purple sweet potato and buni fruit. Natural dye is an alternative that is non-toxic, renewable and easily degraded so that it is friendly to the environment. The results of the efficiency of the DSSC using natural anthocyanins showed good results, namely 0.38%. so it can be concluded that anthocyanins from natural dyes can be used in the manufacture of DSSC. Keywords: Dye Sensitized Solar Cell, Anthocyanins, TiO2 Semiconductor, Natural dye